Identification of coagulation factor (F)X binding sites on the adenovirus serotype 5 hexon: effect of mutagenesis on FX interactions and gene transfer - Alba, Raul (American Society of Hematology, 2009)
Recent studies have demonstrated the importance of coagulation factor X (FX) in adenovirus (Ad) serotype 5–mediated liver transduction in vivo. FX binds to the adenovirus hexon hypervariable regions (HVRs). Here, we perform a systematic analysis of FX binding to Ad5 HVRs 5 and 7, identifying domains and amino acids critical for this interaction. We constructed a model of the Ad5-FX interaction using crystallographic and cryo-electron microscopic data to identify contact points. Exchanging Ad5 HVR5 or HVR7 from Ad5 to Ad26 (which does not bind FX) diminished FX binding as analyzed by surface plasmon resonance, gene delivery in vitro, and liver transduction in vivo. Exchanging Ad5-HVR5 for Ad26-HVR5 produced deficient virus maturation. Importantly, defined mutagenesis of just 2 amino acids in Ad5-HVR5 circumvented this and was sufficient to block liver gene transfer. In addition, mutation of 4 amino acids in Ad5-HVR7 or a single mutation at position 451 also blocked FX-mediated effects in vitro and in vivo. We therefore define the regions and amino acids on the Ad5 hexon that bind with high affinity to FX thereby better defining adenovirus infectivity pathways. These vectors may be useful for gene therapy applications where evasion of liver transduction is a prerequisite.